Health Locus of Control dalam Menjalani Diet pada Pasien Diabetes Mellitus - I Wayan Candra; I Nengah Sumirta (Jurnal Gema Keperawatan, 2016)
The aim of the study to know about health locus is of control i operate in diet at patients diabetes mellitus in puskesmas II west of denpasar.The kind of research this is research descriptive used the cross sectional to technique purposive sampling with a sample of 30 people. Type of data is primary data. The instrument used is Multidimensional Health Locus of Control. The result of this research shows that from 30 respondents, most have external health locus is of control is about 18 respondents (60,0 %), and respondents own internal health locus is of control as many as 12 respondents (40 %), Health locus of control based on their age reveal that the majority of 10 respondents (33.3 %) is at the age range of the 31-59 year having dimensions external health locus of control, health locus of control on the basis of sex reveal that the majority of 12 respondents (40,0 %) gender females have external dimensions health locus of control, health locus of control based on education reveal that the majority of 16 respondents (53,3 %) educated basic dimension external health locus of control, health locus of control by trade show that the majority of 13 respondents (43,3 %) diffusing having dimensions external health locus of control,and health locus of control based on the social economy is showing that the majority of 12 respondents (40,0 ) with income ≤ umk rp .2.007.000 having dimensions external health locus of control.